Inovasi Kemasan dan Branding Kemplang Rawa Lebak Berbasis Digital Marketing - Icuk Muhammad Sakir; Indah Pusnita; Ivana Ivana; Ahmad Ariq Izdihar; Nabila Dhea Anggraini (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to increase the selling value and competitiveness of Rawa Lebak kemplang products through packaging innovation and digital marketing-based branding strengthening for MSME groups in the Rawa Lebak region of South Sumatra. The problems faced by partners are product packaging that is still simple, unattractive, and minimal use of digital platforms for marketing, resulting in limited market reach. The implementation method includes training in modern packaging design that is ergonomic and has local character, mentoring in creating a brand identity, and practical training in using social media and marketplaces for promotion and sales. The results of the activity showed that partners were able to produce new packaging that is more hygienic, informative, and has regional characteristics, and began actively marketing products through Instagram, TikTok, and Shopee. The impact is seen in increased knowledge of partners about branding and digital marketing, increased consumer trust, and increased sales turnover. This activity proves that packaging innovation combined with digital marketing strategies is effective in encouraging the independence and sustainability of local food MSMEs.